Pengaruh Pemberian Esomeprazole Terhadap Ekspresi Imunohistokimia Soluble Fms-Like Tyrosine Kinase (Sflt-1) Dan Soluble Endoglin (Seng) Pada Tikus Dengan Model Preeklamsia - Andri, Sofyan; Aldiansyah, Dudy; Dina, Sarah; Marpaung, Johny; Adenin, Ichwanul; Faradina, Dwi (Fakultas Kedokteran Universitas Riau, 2025)
Preeclampsia is a systemic disorder affecting approximately 3–8% of pregnant women, occurring during or after pregnancy. The exact cause and underlying mechanisms of this condition remain unclear. It is believed that the anti-angiogenic molecules soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng), which are excessively produced by the placenta in preeclampsia, play a significant role in endothelial dysfunction. Recent studies suggest that esomeprazole, a proton pump inhibitor, is generally well tolerated in preeclamptic patients. This study aimed to evaluate the effect of esomeprazole administration on the reduction of sFlt-1 and sEng expression in a preeclampsia-induced rat model using an analytical approach with a quasi-experimental design. The research was conducted at two laboratories within the Faculty of Medicine and the Faculty of Mathematics and Natural Sciences at Universitas Sumatera Utara: the Anatomical Pathology Laboratory and the Biology Laboratory. The study subjects consisted of 30 healthy and active female laboratory rats (Rattus norvegicus), aged 10 weeks, modeled to resemble preeclamptic conditions. The study was carried out in May 2021. After the intervention, significant differences were observed between the intervention and control groups in systolic blood pressure, diastolic blood pressure, and mean arterial pressure (MAP) (p = 0.001; p = 0.014; p = 0.001). Additionally, the proportion of proteinuria was lower in the intervention group than in the control group. The mean expression levels of sFlt-1 and sEng also showed statistically significant differences between the intervention and control groups (p = 0.002; p = 0.001). The findings indicate statistically significant changes in MAP, systolic and diastolic blood pressure, and proteinuria across all groups following the intervention. A comparison of sFlt-1 and sEng expression levels among the negative control, positive control, and intervention groups revealed statistically significant differences. Esomeprazole administration at a dosage of 4.68 mg/kgBW/day significantly reduced sFlt-1 expression, demonstrating the therapeutic potential of esomeprazole in suppressing anti-angiogenic factors in preeclampsia.